The great beyond - Murawiec, Léa, 1994- (Drawn & Quarterly, 2023)
Manel Naher wants out. In a world where your name is currency, it's tough to make ends meet. It's even tougher when you share a name with a rising pop star. The city is unbearable -- endless high-rises, social climbers left and right, and nothing but names as far as the eye can see. But Manel is looking a little bit farther, just beyond the horizon, and she's even convinced her buddy Ali of how much more could be lying in wait right outside city limits. When a sudden heart attack induced by diminished name recognition foils Manel's plans, gradual change becomes a catalyst for a complete lifestyle overhaul. This stylish, absurd comedy of contemporary manners skewers the human condition in persistent self-promo. Sharp, architectural lines are accented by decisively mellow hues, building a humorously grim world unexpectedly bathed in nothing but light. An exciting debut from a fresh perspective, The Great Beyond showcases newcomer Léa Murawiec's command of comics language and satirizes a sprawling metropolis, its politics, and its extraordinary inhabitants.